Preventive Training of Social Skills at School: Development of Social Skills in Adolescents - Grinkevičiūtė, Žaneta; Vyšniauskytė-Rimkienė, Jorūnė (Socialinė teorija, empirija, politika ir praktika, 2013)
SummaryA preventive program of training social skills was developed and implemented in-class for 14–16-year-old adolescents in a regular secondary school. The social skills training program of sixteen workshops was led by a professional social worker. The methods of instruction, modeling, role-playing games, generalization were used to develop social skills of adolescents. In the research, the triangulation method (qualitative and quantitative) was used. The action research revealed that the social skills training program was partially effective. The boys’ behaviour mostly changed according to data of the assertiveness and empathy scales. The boys became more open; moreover, they began to express their feelings and show interest in other peoples’ feelings. Adolescents began to initiate conversations and became assertive in interactions with others. In group work, the girls showed more changes in their behaviour (became more united, were sharing their situations, were actively involed in the group work). According to the data of the research, recommendations were prepared for organizations and institutions working with adolescents in organizing stable and long-term social skills training sessions including participants with different levels of social competence development.Key words: social skills, preventive training of social skills, training of social skills at school.